Effect of nitrogen fertilizer rate and timing on sorghum productivity in Ethiopian highland Vertisols - Bayu, Wondimu; Ziadat, Feras M.; Strohmeier, Stefan; Zucca, Claudio; Tefera, Meron; Ayalew, Baye; Klik, Andreas; Demelash, Nigus (Informa UK Limited, 2018)
Sorghum is cultivated on Vertisols in the Ethiopian Highlands. An experiment was conducted in the Gumara-Maksegnit watershed in 2013 and 2014 to assess the effect of rate and timing of nitrogen fertilizer application on the possibility to shorten the maturity period and to improve the productivity of sorghum. The experiment was laid out as Randomized Complete Block Design with three replications. Treatments were nitrogen doses between 0 and 87 kg N ha-1 as urea applied at planting, at knee-height stage or in split doses at both stages. Results showed that application of 23, 41, 64 and 87 kg ha-1 N gave a yield increase of 40, 53, 62 and 69% over the control (0 kg N ha-1), respectively. In addition, split application of 41 kg ha-1, 64 kg ha-1 and 87 kg ha-1 of nitrogen fertilizer, half at planting and half at knee height stage, gave 19%, 15% and 18% increase in sorghum grain yield over a single dose application, respectively. Applying 87 kg ha-1 nitrogen fertilizer with split application half at planting and half at knee height stage, along with 46 kg ha-1 of P2O5, gave the highest grain yield and income.